TINJAUAN HUKUM WANPRESTASI OLEH NASABAH PERJANJIAN KREDIT KUPEDES PADA PT. BANK RAKYAT INDONESIA UNIT SUDIRMAN PEKANBARU - Muhammad Nadhif Syauqi Abrar; Hayatul Ismi; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The problem that often arises in the implementation of credit agreements is asituation where the debtor is negligent in carrying out his obligations or what is usuallycalled default. The fact that often occurs in the field is that debtors are late in makingpayments, both installments and interest. Therefore, every time the bank extends credit, inpractice the bank always asks the debtor to submit collateral. . For security in returningthe credit. Credit given by banks is based on trust, so that in this way credit is giving trustto customers. . Research Objectives To find out the process of efforts and obstacles insolving default problems by customers of the Kupedes credit agreement at PT. Bank RakyatIndonesia Unit Sudirman Pekanbaru.This type of research can be classified as a Juridical Sociological type of research,because in this study the authors directly conducted research at the location or place understudy in order to provide a complete and clear picture of the problem under study. Thisresearch was conducted at PT. Bank Rakyat Indonesia Sudirman Pekanbaru Unit Branch,while the population and sample are all parties related to the problems studied in thisstudy, the data sources used are primary data, secondary data, research subjects, relatedto data collection in this study by observation, interviews and studies literature.As for defaults in the process of bank credit agreements where the debtor is slow topay credit installments, the bank is negligent and less thorough in assessing potentialdebtors. Dispute resolution is divided into two, namely litigation and non-litigation.Dispute resolution through litigation is a settlement of disputes that is carried out througha court, where this settlement must follow formal requirements and procedures in courtand as a result the time period for resolving disputes is longer. As a party, Bank RakyatIndonesia knows the prospective debtor well in terms of personality, ability, capital,collateral, economic conditions, so there is little possibility of bad financing. If the debtordisappears / where his whereabouts are unknown while he still has debts to the bank /creditor. The trick is to provide a blacklist (input into a blacklist book).